Estrategias didácticas activas en Ciencias Naturales para séptimo grado de la Unidad Educativa " 19 de Septiembre". - Hinojosa Chávez, Patricia Noemí (2021)
The present investigative work deepened the active didactic strategies for the learning of Natural Sciences in the seventh grade students in the Unidad Educativa "19 de Septiembre", because education is a process of constant change and modernization that allowed educational approaches to be reformulate and create new needs in the way of teaching and learning with an evolved curriculum; the problem was that the teaching process is loaded with traditionalism in its methodology, limited interest of the students and limited training of teachers, it was necessary to incorporate new didactic strategies in the teaching-learning processes. The research objective proposed to delineate active didactic strategies for the learning of Natural Sciences in seventh grade students. The methodological design was qualitative and non-experimental due to the research was directly involved in the virtual school environment, the general methods used are deduction, synthesis, documentary analysis, as a technique the interview was developed with focus groups made up of 7 to 10 students handled throughout the study journey. The results achieved suggested the approach of a proposal oriented to an action guide for obtaining the learning of Natural Sciences as support for the teacher to generate the training process in a more active way. It was concluded that the active didactic strategies responded to a tangible problem in the Educational Unit, due to the motivation that the students found in the journey of the training process, increased empathy and collaboration